2019
DOI: 10.1101/621763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution and expansion of multidrug resistant malaria in Southeast Asia: a genomic epidemiology study

Abstract: Summary Background A multidrug resistant co-lineage of Plasmodium falciparum malaria, named KEL1/PLA1, spread across Cambodia c.2008-2013, causing high treatment failure rates to the frontline combination therapy dihydroartemisinin-piperaquine. Here, we report on the evolution and spread of KEL1/PLA1 in subsequent years. Methods We analysed whole genome sequencing data from 1,673 P. falciparum clinical samples collected in 2008-2018 from northeast Thailand, Laos, Cambodia and Vietnam. By investigating genom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, long-term use of anti-malarial drugs particularly PPQ induced ADR [14]. Previous studies indicated that several mutations of pfcrt (93S, 97Y, 101F, 145I, 343L, 353 V, and 356 T) were related to reducing parasite sensitivity to PPQ [13,14,[36][37][38][39]. In this study, no mutations were detected at loci 93, 97, 101, 145, 343, 350, and 353.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…However, long-term use of anti-malarial drugs particularly PPQ induced ADR [14]. Previous studies indicated that several mutations of pfcrt (93S, 97Y, 101F, 145I, 343L, 353 V, and 356 T) were related to reducing parasite sensitivity to PPQ [13,14,[36][37][38][39]. In this study, no mutations were detected at loci 93, 97, 101, 145, 343, 350, and 353.…”
Section: Discussionmentioning
confidence: 41%
“…Thus, the effect of PPQ cannot be ignored. However, long-term use of anti-malarial drugs particularly PPQ induced ADR [14]. Previous studies indicated that several mutations of pfcrt (93S, 97Y, 101F, 145I, 343L, 353 V, and 356 T) were related to reducing parasite sensitivity to PPQ [13,14,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, ART treatment failure has reached endemic status in SEA (1, 4, 5) and has seemingly emerged in Africa (6). More worryingly, parasites carrying both ART and partner drug piperaquine resistance mutations, have been reported in SEA threatening the current mainstay of ACTs (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…By using drugs in combination with different targets the intention is to delay the emergence of resistance to the individual components. However, recent evidence has emerged in the Greater Mekong subregion of resistance to both artemisinin (3,4) and current partner drugs (5,6). There is, therefore, an urgent need to develop new drugs and novel combination regimens before reduction in ACT efficacy occurs more widely.…”
Section: Introductionmentioning
confidence: 99%